Letter : Purchase of surgical instruments for Spain - Schevenels, Walther, b. 1894
041-0132-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President: W.M. Citrine, Great Britain Vice-Presidents: H. Jacobson, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W. Schevenels Letter Sit. Espagne No 173 Sch/H 27th October 1936. Mr. H.V. Tewson, LONDON. Dear Comrade Tewson, PURCHASE OF SURGICAL INSTRUMENTS FOR SPAIN: With reference to your letter of the 24th October, on the above subject, we have already transmitted to our Central Committee in Madrid the information about the constitution of the Information Bureau in London by the Catalonian Office of Propaganda. We have also asked the Committee to let us know what attitude we should adopt towards this Information Bureau, and what action we should take as regards the purchase of surgical instruments for Barcelona. As soon as we receive a reply from Madrid, we will let you know. As far as Paris is concerned, we know that a similar Information Bureau has been set up here but up till now it has not got into touch with us. Yours sincerely, W. Schevenels, General Secretary: Enc: Correspondence on surgical instruments, which we return. 292/946/41/132